Federal funds rate and the Taylor Rule after the introduction of the new monetary policy framework in 2020 - Malina, Marek; Potužák, Pavel; Chytil, Zdeněk, 1949-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
The primary objective of this thesis is to examine the extent to which the Federal Reserve adheres to the Taylor rule in its monetary policy decisions. A secondary aim is to assess the influence of inflation targeting on policy conduct. Using official Federal Reserve data, various Taylor rule models are constructed and analyzed. The analysis suggests that the Federal Reserve primarily relies on discretionary policy rather than strict adherence to rule-based frameworks, as evidenced by frequent violations of the Taylor principle. Inflation targeting appears to have very limited effect on the conduct of monetary policy. Smoothed version of the Taylor rule aligns more closely with observed policy behavior than the original specification.
Vedoucí práce: Pavel Potužák
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses